A multi-objective approach to incorporate indirect costs into optimisation models of waterborne sewer systems - Bester, Albertus J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2011.